Absorption capacity and toxicity of paper points after sterilization - Mirian Marubayashi Hidalgo; Ivaldo Gomes de Moraes; Clóvis Monteiro Bramante; Lurdes Botelho Garcia; Marlice Lukiantchuk; Fausto Rodrigo Victorino (Faculdade São Leopoldo Mandic, 2008)
Objective: To evaluate the influence of the sterilization process on paper cones as regards their absorption capacity, and consequently, root canal drying, in addition to the possible release of any antimicrobial or cytotoxic product. Methods: The cones used were of three of the brands found on the Brazilian market Dentsply (Dentsply Indústria e Comércio Ltda., Petrópolis, Brazil), Endopoints (Endopoints Indústria e Comércio Ltda., Paraíba do Sul, Brazil) and Tanari (Tanari Industrial Ltda., São Paulo, Brazil). To evaluate the absorption capacity, the cones were submitted to four sterilization cycles, and the modified Holland technique was performed. The antimicrobial/cytotoxic capacity was verified by means of depositing the sterilized cones in Petri dishes containing Miller-Hinton Agar and Blood Agar, seeded with S.aureus and E. coli. Results: The Dentsply (Dentsply Indústria e Comércio Ltda., Petrópolis, Brazil) and Tanari (Tanari Industrial Ltda., São Paulo, Brazil)cones presented greater absorption after the first sterilization cycle, followed by a drop in the second and third cycles, and a new increase in the fourth cycle. For the Endopoints (Endopoints Indústria e Comércio Ltda., Paraíba do Sul, Brazil) cones, the values were inverted, with a small drop in absorption after the first cycle, increase in the second and third cycles, and a new drop in the fourth cycle. None of the cones presented antimicrobial activity after the sterilization process. Conclusion: The sterilization process by damp heat does not alter the properties of absorption and there is no release of by-products from the tested paper cones.